Clinical assessment of coiled fiducial markers as internal surrogates for hepatocellular carcinomas during gated stereotactic body radiotherapy with a real-time tumor-tracking system. Issue 1 (April 2017) - Hanazawa, Hideki; Takahashi, Shotaro; Shiinoki, Takehiro; Park, Sung Chul; Yuasa, Yuki; Koike, Masahiro; Kawamura, Shinji; Shibuya, Keiko
Abstract: Background and purpose: To report the clinical usefulness of coiled fiducial markers as an internal surrogate in gated stereotactic body radiotherapy (SBRT) for hepatocellular carcinoma (HCC) using a real-time tumor-tracking radiotherapy (RTRT) system. Materials and methods: Seventeen HCC patients with Child-Pugh (CP) scores of A or B received gated SBRT (45–50 Gy in 5–10 fractions) using an RTRT system and Visicoil markers. Local control (LC), progression-free (PFS), and overall survival (OS) rates were assessed using the Kaplan-Meier method. Toxicities were assessed using the Common Terminology Criteria for Adverse Events, Version 4.0. Results: Of the 17 patients, 14 had a CP score A. The mean planning target volume was 54.6 cc. Only 1 patient developed pneumothorax after marker implantation. Visicoil tracking during SBRT was possible in all cases. With a median follow-up of 16 months, 1-year LC, PFS, and OS rates were 100%, 53%, and 82%, respectively. Grade ≥ 2 late toxicity was observed in 2 patients (grade 2 duodenal ulcer and grade 3 temporary transaminase elevation). Conclusions: Using an RTRT system and Visicoil markers, gated SBRT was well tolerated in patients with HCC. This can be considered a safe treatment strategy with potential for delivering favorable outcomes.